Does The Characteristics Of The Auditor Effect Audit Quality? - Suryandari, Ni Nyoman Ayu; Arie Susandya, Anak Agung Putu Gede Bagus (Journal Research of Social Science, Economics, and Management, 2023)
The purpose of this study is to determine the effect of the auditor's characteristics such as spiritual intelligence, competence, experience, independence, and professional skepticism on audit quality. The sample in this study is 108 respondents which come from all auditors in accounting firms in Bali. The analysis technique used in this study is multiple linear regression. The results showed that spiritual intelligence has a positive effect on audit quality. On the other hand, competence, experience, independence, and professional skepticism does not effect audit quality. This study implies that an auditor who has high spiritual intelligence will be able to act and behave ethically in his profession and organization. Spiritual intelligence makes individuals able to distinguish between good and bad actions. In conducting audit examinations, spiritual intelligence will influence the auditor to act following the code of ethics and the accounting profession. Spiritual intelligence is able to avoid actions that can reduce audit quality.